ASUPAN Fe, KEBIASAAN MINUM TEH, DAN STATUS GIZI BERKAITAN DENGAN KEJADIAN ANEMIA PADA SANTRI PUTRI - Kusumawati, Agustin Dyah; Nurhayati, Nurhayati; Hardiansyah, Angga (Journal of Nutrition College, 2024)
ABSTRACTBackground: Anemia must receive special attention because it can affect health status, especially in women. Anemia can be caused by a lack of consuming foods containing iron (Fe), vitamin C, protein, the habit of consuming Fe inhibitor substances such as caffeine, oxalate, phytate, and tannins contained in tea as well as other factors such as blood loss and nutritional status.Objectives: To determine the relationship between Fe intake, tea-drinking habits, and nutritional status with the incidence of anemia in female students.Methods: This research used a cross-sectional design with a total sample of 73 female students at the Sirojuth Tholibin Islamic Boarding School in Grobogan Regency, Central Java. The sample was collected with accidental sampling. Data on Fe intake were obtained using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), tea-drinking habits using the Food Frequency Questionnaire (FFQ), nutritional status using Body Mass Index by Age (BMI/U), and the incidence of anemia was determined by measuring hemoglobin using the Point of Care Testing (POCT) method with the easytouch GCHb digital device. Bivariate analysis with Gamma (g) correlation test.Results The results of this study obtained the characteristics of respondents with sufficient Fe intake 41 (56,2%) respondents, good tea-drinking habits 51 (69.9%) respondents, good nutritional status 54 (74%) respondents, and no anemia category 52 (71.2%) respondents. Based on the results of the bivariate test analysis, it showed that Fe intake, tea-drinking habits, and nutritional status had a relationship with the incidence of anemia (p-value <0.05). Conclusion: There is a relationship between Fe intake, tea-drinking habits, and nutritional status with the incidence of anemia in female students.Keywords : anemia; Fe intake; female students; nutritional status; tea-drinking habit.                                                                      ABSTRAKLatar belakang: Anemia harus mendapat perhatian khusus karena dapat memengaruhi status kesehatan khususnya pada perempuan. Anemia dapat disebabkan oleh kurangnya mengonsumsi makanan yang mengandung zat besi (Fe), vitamin C, protein, kebiasaan konsumsi zat inhibitor Fe seperti kafein, oksalat, fitat dan tanin yang terkandung dalam teh serta faktor lain seperti kehilangan darah dan status gizi.Tujuan: Mengetahui hubungan antara asupan Fe, kebiasaan minum teh, dan status gizi dengan kejadian anemia pada santri putri.Metode: Penelitian ini menggunakan desain cross sectional dengan total sampel 73 santri putri di Pondok Pesantren Sirojuth Tholibin di Kab. Grobogan, Jawa Tengah. Sampel diambil dengan teknik accidental sampling. Data asupan Fe diperoleh dengan menggunakan Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), kebiasaan minum teh dengan Food Frequency Questionnaire (FFQ), status gizi dengan Indeks Massa Tubuh menurut Umur (IMT/U), dan kejadian anemia ditentukan dengan pengukuran hemoglobin menggunakan metode Point of Care Testing (POCT) dengan alat digital Easytouch GCHb. Analisis bivariat dengan uji korelasi Gama (g).Hasil: Hasil penelitian ini diperoleh karakteristik responden dengan asupan Fe cukup 41 responden (56,2%), kebiasaan minum teh baik 51 responden (69,9%) status gizi baik 54 responden (74%), dan kejadian anemia dengan kategori tidak anemia 52 responden (71,2%). Berdasarkan hasil analisa uji bivariat menunjukkan bahwa asupan Fe, kebiasaan minum teh, dan status gizi memiliki hubungan dengan kejadian anemia (nilai p<0,05).Simpulan: Terdapat hubungan antara asupan Fe, kebiasaan minum teh, dan status gizi dengan kejadian anemia pada santri putri.Kata Kunci : anemia; asupan Fe; santri putri; status gizi; kebiasaan minum teh.